Rancang Bangun Sistem Informasi Pengaduan PPDB Kantor Cabang Dinas Pendidikan Wilayah XI Provinsi Jawa Barat Berbasis Web - Rosliani, Elin; Maulana, Andriansyah; Nugraha, Yopi; Ependi, Devina Nur (JATISI, 2024)
Kantor Cabang Dinas Pendidikan (KCD) Wilayah XI needs an information system to serve complaints about new student admission activities (PPDB) in Region Because during the implementation of new students (PPDB) there are various kinds of violations that occur. Such as dealing with Family Card domiciles, buying and selling seats, illegal levies, entrustments from officials. Therefore, an information system is needed that can serve complaints about new student admission activities (PPDB) in Region XI. The information system was designed using UML diagrams and built using the Laravel framework with data storage using the MySQL DBMS. By designing a complaint information system for new student admissions, it can make it easier for the public to carry out supervision using the web. Keywords— KCD, PPDB, Laravel, UML, Information System